Landcover Quality Detection Using Segmentation And Content Base Image Retrieval Methods - Dwi Handoko; Suhendro Y Irianto; Sri Karnila (Proceeding International Conference on Information Technology and Business, 2019)
This paper tries to explore level and accuracy Content Based Image Retrieval method on Landsat imaginary. The images include an areal photography and land satellite photoraphy or Landsat which widely used and recognize for spatial information analysis. The analysis uses mapping of situation or state of earth’s surface, particularly the land surface. Landsat can be used to create topographic map, determining of attitude or height model of a certain place in the earth. Aerial photographs are used to detect changes of earth surface, in this work the changes by using Content Based Image retrieval or CBIR. The accuracy changes measurement calculate using precision and recall parameters. In this paper, Landsat images also used to detect the appear and dis appear of vegetation and other objects on the earth. More than 100 Landsat images used in this work, and around 15 images was use d as queries. The results show that accuracy of image retrieval is a quite good , which more 75%.Keywords: Landsat Images, CBIR, Precision Recall